On the Regularity of Weak Contact p-Harmonic Maps. (29th January 2013) - Dragomir, Sorin; Petit, Robert
Abstract : We prove Caccioppoli type estimates and consequently establish local Hölder continuity for a class of weak contact ( 2 n + 2 ) -harmonic maps from the Heisenberg group ℍ n into the sphere S 2 m − 1 .